Somatic MMR Gene Mutations as a Cause for MSI‐H Sebaceous Neoplasms in Muir–Torre Syndrome‐Like Patients. Issue 3 (13th March 2015) - Joly, Marie‐Odile; Attignon, Valéry; Saurin, Jean‐Christophe; Desseigne, Françoise; Leroux, Dominique; Martin‐Denavit, Tanguy; Giraud, Sophie; Bonnet‐Dupeyron, Marie‐Noëlle; Faivre, Laurence; Auclair, Jessie; Grand‐Masson, Chloé; Audoynaud, Carole; et al.
ABSTRACT: Sebaceous neoplasms are a major clinical feature of Muir–Torre syndrome (MTS) associated with visceral malignancies, especially colorectal and endometrial tumors. The diagnosis of MTS relies largely on the microsatellite instability (MSI) phenotype in tumors, suggesting germline mutations in DNA mismatch repair (MMR) genes responsible for the inherited disease. We hypothesized that in some MSI‐H sebaceous tumors, acquired rather than inherited mutations in MMR genes could be involved. Using next‐generation sequencing, we screened MMR gene mutations in 18 MSI‐H sebaceous tumors. We found mutations in 17 samples (94%). Indeed, 12/17 (71%) were shown to carry acquired somatic mutations and among 12 samples, seven were shown to be associated with additional somatic alterations like loss of heterozygosity or multiple mutations, suggesting somatic second hits. Our findings strongly suggest that somatic MMR deficiency is responsible for a proportion of MSI‐H sebaceous tumors.